PENGARUH ELECTRONIC WORD OF MOUTH (eWOM) TERHADAP KEPUTUSAN PEMBELIAN KAMERA DSLR - Tommi Wijaya; Eristia Lidia Paramita (Jurnal Manajemen., 2014)
The ever-growing world of photography led to a large number of owners of DSLR cameras. The photographic community is formed. Technological progress in terms of the internet and social network Facebook gives impact on the development of photography community. The Internet empowered consumers share information easily. Consumers share their experiences through the internet, so that it affects others by using the electronic word of mouth. It is againsts buying decision on a product. This study aimed to know the influence of the electronic word of mouth on Komunitas Kamera Apa Saja (KOKAS) in Facebook groups to the decision purchase of DSLR cameras.30 respondents were done with judgement sampling techniques. The simple linear regression was used to analyze the data. The result showed that the electronic word of mouth did not affect significantly the purchase decisions of DSLR cameras. The hypothesis test results (test t) value reaches the significance of 0.063 & gt; with the R square value of 0.005 and 11.8%.